The Silent Strategy and its Role in Undermining Political Systems : (The United States of America is A Model) (قضايا سياسية, 2024)
The concept of smart power, which was introduced in 2003 AD to indicate the ability to combine hard power and soft power in one strategy for influence, was called the silent strategy, and it is available to state and non-state actors. This concept lies at the core of the process of power transformation, as some countries have many sources of capacity, but it fails to transform them into outcomes that benefit the state. The importance of the context that is used in smart power strategies comes from the focus on what is called contextual intelligence and its importace for silent strategic. It means possessing the skills and experiences that help the external policy maker plan tactics with goals to create this fusion strategy that combines hard power and soft power.